Case Report: Two-month-old infant with PHACE syndrome: facial hemangioma and severe complex coarctation of the aorta - David, Sánchez-Ortiz; Lucía, Deiros-Bronte; Lucía, De la Hoz-Marañón; Marta, Feito-Rodríguez; Juvenal, Rey-Lois; Diana, Salas-Mera; Carlos, Labrandero-De Lera; Juan Carlos, López-Gutiérrez; Federico, Gutiérrez-Larraya (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPHACE syndrome is an uncommon disorder, marked by large segmental hemangiomas on the face and various developmental anomalies. Significant advancements have been made in its diagnosis, imaging, and understanding of complications since 1996.Case SummaryWe describe the first diagnosis case of PHACE syndrome in a one-month and 19-day-old infant who presented with a large facial hemangioma and coarctation of the aorta originating from the left common carotid artery, along with an aberrant course of the right subclavian artery. The complementary diagnostic studies, their surgical correction, and their progression are described.DiscussionGiven the rarity of the syndrome (the PHACE Syndrome International Clinical Registry and Genetic Repository has over 270 enrolled individuals) and the importance of early diagnosis of some anomalies it comprises, particularly cardiovascular anomalies, dissemination is considered crucial for general and pediatric cardiologists.